Adherence to Antihypertensive Medication in Treatment‐Resistant Hypertension Undergoing Renal Denervation - Schmieder, Roland E. (J Am Heart Assoc, 2016)
BACKGROUND: Adherence to medication has been repeatedly proposed to represent a major cause of treatment‐resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control. METHODS AND RESULTS: Eighty patients with TRH were included in 2 prospective observational studies that assessed the difference of potential antihypertensive and nephroprotective effects of renal denervation. To compare prescribed with actual medication intake (representing a measure of adherence), we analyzed urine samples collected at baseline and at 6 months after renal denervation for antihypertensive compounds or metabolites (by liquid chromatography–mass spectrometry). In addition to office BP, 24‐hour ambulatory BP and central hemodynamics (central systolic pressure, central pulse pressure) were assessed. Informed consent for analyses of urine metabolites was obtained from 79 of 80 patients. Actual intake of all antihypertensive drugs was detected at baseline and at 6 months after renal denervation in 44 (56%) and 52 (66%) patients, respectively; 1 drug was missing in 22 (28%) and 17 (22%) patients, respectively, and ≥2 drugs were missing in 13 (16%) and 10 (13%) patients, respectively. At baseline, 24‐hour ambulatory BP (P=0.049) and central systolic BP (P=0.012) were higher in nonadherent patients. Adherence did not significantly change overall (McNemar‐Bowker test, P=0.362). An increase in adherence was observed in 21 patients, and a decrease was observed in 11 patients. The decrease in 24‐hour ambulatory BP was not different in those with stable adherence 6 months after renal denervation (n=41, −7±13 mm Hg) compared with those with increased adherence (n=21, −10±13 mm Hg) and decreased adherence (n=11, −7±14 mm Hg) (P>0.20). Our study is limited by the relatively small sample size and potentially by the specific health environment of our university center (Northern Bavaria, Germany). CONCLUSIONS: Nonadherence to medication among patients with TRH was relatively low: ≈1 of 6 patients with TRH did not take ≥2 of the prescribed drugs. Adherence pattern did not change significantly after renal denervation and had no impact on the overall observed BP changes, supporting the concept that renal denervation is an effective treatment in patients with TRH. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifiers: NCT00888433, NCT01442883 and NCT01687725.